Zasada chrystocentryzmu w kaznodziejstwie - Twardy, Jan (Śląskie Studia Historyczno-Teologiczne, 2011)
The rule of Christocentrism has strong biblical basis and is deeply rooted in contemporary theology – which is also reflected in homiletics.As the preacher should bring a full image of C hrist (totus Christus) closer to the faithful, the author presents five aspects of homiletic Christocentrism.So it is a theocentric aspect – as proclaiming Jesus leads towards doctrine of One God; it is also a Trinitarian aspect – as acting of separate Divine Persons should be emphasized in a sermon. Christ established the Church, is her Head and acts in her through Holy Spirit, so Christocentrism has an ecclesial aspect. The pneumatological dimension is connected with this aspect because Holy Spirit makes present the saving work of Christ and helps the priests to actualize the Gospel. It is necessary to speak about Mother of God and about saints in the spirit of Christocentrism, stressing their union with Saviour and total fulfilment of His Gospel. The Christocentric dimension exists in the preacher’s mystagogy - as in it we instruct the faithful that in liturgy of the C hurch the Paschal mystery of Christ is present and trough it appears His salutary power. For the whole Christians life is in the close union with Christ who trough Holy Spirit leads God’s people towards sanctity. The word ministry is drawing „to sum up all things in Christ, in heaven an on earth” (Eph 1:10).